2022
DOI: 10.46568/bios.v3i2.96
|View full text |Cite
|
Sign up to set email alerts
|

Risk of COVID-19 infection and severity of clinical outcomes and its association with ABO blood groups

Abstract: Objective: To determine association of ABO blood groups with severity of COVID-19 symptoms among covid recovered patients of different blood type. Methodology: An observational/experimental study was conducted at department of physiology, Sindh university Jamshoro from April 2021 to December 2021.The sample size (n) was 732, data consist of male and female covid recovered participants of age group 18-30yrs. Self -structured questionnaire was used to evaluate intensity of symptoms of COVID 19 and for other char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Our study found that students were reluctant to seek help during online sessions, leading to a communication gap and a poor learning experience. Likewise, Shah et al (2021) investigated the difficulties associated with E-learning in Pakistan amid the COVID-19 pandemic and identified that universities in Sindh face inadequacies in e-learning due to challenges related to internet accessibility, electricity availability, student-teacher engagement, and the capability to actively participate and raise questions in online learning environments. These findings align…”
Section: Discussionmentioning
confidence: 99%
“…Our study found that students were reluctant to seek help during online sessions, leading to a communication gap and a poor learning experience. Likewise, Shah et al (2021) investigated the difficulties associated with E-learning in Pakistan amid the COVID-19 pandemic and identified that universities in Sindh face inadequacies in e-learning due to challenges related to internet accessibility, electricity availability, student-teacher engagement, and the capability to actively participate and raise questions in online learning environments. These findings align…”
Section: Discussionmentioning
confidence: 99%